2020
DOI: 10.1002/hpja.372
|View full text |Cite
|
Sign up to set email alerts
|

Concerns about vitamin D and sun exposure behaviour among Australians

Abstract: The main source of vitamin D is skin synthesis following exposure to ultraviolet radiation (UVR), 1 over-exposure to which is also a risk factor for skin cancer. 2 Vitamin D has a long-established important role in musculoskeletal health. 3 However, the past two decades have witnessed a dramatic rise in epidemiological research on emerging and potential non-skeletal health benefits of vitamin D, 4 challenging recommended optimal levels of sun exposure. 5 Findings for a protective role of vitamin D for cardiova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 43 publications
(103 reference statements)
0
7
0
Order By: Relevance
“…It is unlikely that males and adolescents’ inferior use of physical sun protection would be offset by extensive use of sunscreen. The National Sun Protection Survey shows similar prevalence of sunscreen use among Australian adolescents and adults, and lower prevalence in men than women (Tabbakh & Dobbinson, 2018). Variation in personal sun protection between males and females in the present study may be primarily attributable to clothing norms and trends, but risk taking, resistance to protective behaviors, and lower health concerns among men may also play a role (Courtenay, 2000; Courtenay et al, 2002; Deeks et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…It is unlikely that males and adolescents’ inferior use of physical sun protection would be offset by extensive use of sunscreen. The National Sun Protection Survey shows similar prevalence of sunscreen use among Australian adolescents and adults, and lower prevalence in men than women (Tabbakh & Dobbinson, 2018). Variation in personal sun protection between males and females in the present study may be primarily attributable to clothing norms and trends, but risk taking, resistance to protective behaviors, and lower health concerns among men may also play a role (Courtenay, 2000; Courtenay et al, 2002; Deeks et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Studies undertaken in Australia have found that almost 50% of people believe that using sun protection limits the ability to produce vitamin D, people are confused about using sunscreen, and very little guidance is provided by health professionals in relation to balancing the harms and risks of sun exposure. 33,34 This emphasises that sun exposure messaging and policies should be refocused to clearly communicate both the risks and benefits of sun exposure to improve overall health outcomes. 35 Spending time outdoors confers benefits beyond those related to vitamin D. Some of these may be induced by the UV-B wavelengths, but others, particularly those related to circadian rhythm, are likely to be mediated by other wavelengths.…”
Section: Discussionmentioning
confidence: 99%
“…While a recent review found that use of low-sun protection factor sunscreens did not appear to negatively affect 25(OH)D concentration, the effect of higher-sun protection factor sunscreens, which are commonly available and recommended for use in Australia, remains unclear (43) . Recent analysis of data from National Sun Protection Surveys from 2010 to 2011, 2013 to 2014 and 2016 to 2017 showed that older Australians were more likely than younger Australians to be concerned about their vitamin D status and less likely than younger Australians to use sunscreen (44) . Although the sample for each study year was found to be representative of the general Australian population with regard to skin type (44) , these findings may not represent sunscreen use practices in the Aboriginal and Torres Strait Islander population.…”
Section: Discussionmentioning
confidence: 99%
“…Recent analysis of data from National Sun Protection Surveys from 2010 to 2011, 2013 to 2014 and 2016 to 2017 showed that older Australians were more likely than younger Australians to be concerned about their vitamin D status and less likely than younger Australians to use sunscreen (44) . Although the sample for each study year was found to be representative of the general Australian population with regard to skin type (44) , these findings may not represent sunscreen use practices in the Aboriginal and Torres Strait Islander population. To our knowledge, there are no data on sunscreen use in the Aboriginal and Torres Strait Islander population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation